Localidades fossílíferas da formação Pirabas ( Mioceno inferior ) e o estabelecimento de unidades paleoecológicas e eventos biológicos - SANTOS, André Augusto Rodrigues (2019)
This work deals the paleobiologic studies developed in the Pirabas Formation based on data recompilation and latter analysis according the concepts and technics in analysis basins and historical paleobiogeography. Were studied twenty localities in Pará state and six at Maranhão and Piauí states, that occur in well exposed along coastal cliffs, road cuts, mines and the subsurface. The paleobiological analysis combined with the historical paleobiogeography allowed recognize the global bioevents of the radiation and geographic spreanding in the Phyllum Mollusca and the innovation on the order Sirenia. In regional dimension are recognized the bioevents of the radiation and geographical spreading in bivalvs, gastropods, decapoda crustacean, echinoids and bryozoans, as well as geographical spreading in the ostracods and the radiation in the planktonic foraminífera. The research also reveals local bioevents individualized in the stenobhiontic and florule specially developed as response the environmental evolution and the great intraspecific variation. The ecostratigraphic analysis is the results of the combination at data providing the subdivison in five ecozones interpreted as a record of prograding deposits experiecing low subsidence. The depositional system is related with incised valley estuarine setting.